Factors associated with contemporary fatherhood - Hershkovitz-Freudenthal, Adi; Lavenda, Osnat (Frontiers in Psychology, 2024)
The most prevalent conceptualization of parenting of our time is intensive parenting which refers to parents' overinvolvement in children's lives, placing the child's needs before others' needs, including the needs of the parents themselves (i.e., Childcentrism). Intensive parenting is mostly attributed to mothers as they are still bearing the bulk responsibility for child rearing. Nevertheless, as the role of fathers changed in recent decades it is crucial to examine intensive parenting among fathers and understand whether factors that are associated with intensive mothering are associated with intensive fatherhood as well. The current study uses Belsky's Process of Parenting model to fill-in the gap. Participants were 301 Israeli fathers of preschool children aged 22 to 50 years old (M=36.34, SD=5.01). They filled out online self-report questionnaires dealing with intensive parenting style, child temperament, social support, marital satisfaction, and parental self-efficacy. The model explained 64% of paternal child-centrism. Fathers who reported having children with more difficult temperament, reported low social support, low marital satisfaction, and low self-efficacy, were more intensive in their parenting style. The present findings are discussed in relation to previous findings regarding maternal child-centrism with an emphasis on their important implications for professionals working with families for the benefit of parents' and children's wellbeing.